2020
DOI: 10.3390/w12071905
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Environment Evaluation of Forest Ecosystem Nature Reserves Using an Unweighted Cloud Model

Abstract: The ecological environment is the foundation of human survival and development, and forest ecosystem nature reserves play an important role in the protection of the ecological environment. The evaluation of forest ecosystem nature reserves facilitates the formulation of relevant management policies. At present, the evaluation of the ecological environment of forest ecosystem nature reserves is mainly based on detailed evaluation of some elements of the ecological environment, rather than on a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Scientific and objective evaluation of ecological environment quality is particularly important, which can provide a strong scientific basis for monitoring, protecting and governing the ecological environment [1][2][3] . A variety of ecological environment assessment methods have been used to monitor and assess the current state and changes in the quality of the ecological environment, among which the establishment of models such as hierarchical analysis and "pressure-state-response" (PSR) have problems such as subjectivity, difficulty in collecting indicator data, and limited coverage 4,5 . In recent years, with the continuous development of satellite remote sensing technology and the accumulation of massive data, it has been widely used in ecological environment quality analysis and assessment due to its many advantages such as speed, timeliness, objectivity and wide spatial coverage 6 .…”
Section: Rsei-based Monitoring Of Ecological Quality and Analysis Of ...mentioning
confidence: 99%
“…Scientific and objective evaluation of ecological environment quality is particularly important, which can provide a strong scientific basis for monitoring, protecting and governing the ecological environment [1][2][3] . A variety of ecological environment assessment methods have been used to monitor and assess the current state and changes in the quality of the ecological environment, among which the establishment of models such as hierarchical analysis and "pressure-state-response" (PSR) have problems such as subjectivity, difficulty in collecting indicator data, and limited coverage 4,5 . In recent years, with the continuous development of satellite remote sensing technology and the accumulation of massive data, it has been widely used in ecological environment quality analysis and assessment due to its many advantages such as speed, timeliness, objectivity and wide spatial coverage 6 .…”
Section: Rsei-based Monitoring Of Ecological Quality and Analysis Of ...mentioning
confidence: 99%
“…Scientific and objective evaluation of ecological environment quality is particularly important, which can provide a strong scientific basis for monitoring, protecting and governing the ecological environment 1 – 3 . A variety of ecological environment assessment methods have been used to monitor and assess the current state and changes in the quality of the ecological environment, among which the establishment of models such as hierarchical analysis and "pressure-state-response" (PSR) have problems such as subjectivity, difficulty in collecting indicator data, and limited coverage 4 , 5 . In recent years, with the continuous development of satellite remote sensing technology and the accumulation of massive data, it has been widely used in ecological environment quality analysis and assessment due to its many advantages such as speed, timeliness, objectivity and wide spatial coverage 6 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the consensus on the ecological environment in previous studies and the characteristics of the study area. Literature [18] established a quantitative evaluation index system for the comprehensive ecological environment of forest ecosystem nature reserve based on water, air, soil and biological environment, constructed a weightless cloud model, and provided a weightless evaluation mechanism. The results showed that the results of this study can provide theoretical support for the evaluation of forest ecosystem nature reserves and general evaluation when the weight is difficult to determine or uncertain.…”
Section: Introductionmentioning
confidence: 99%